A Small-Amplitude Control Method of the Nonlinear Energy Sink Vibration Absorption System - Qingchao Yang; Shuang Li; Jingjun Lou (Shock and Vibration)
The nonlinear energy sink (NES) is an effective method to weaken or eliminate the line spectra feature of ship machinery equipment. However, due to the strong nonlinearity of the NES, there are multistable attractors in the NES vibration absorption system. Moreover, when the excitation characteristics or working conditions of the mechanical equipment change, the NES may migrate from the small-amplitude motion state to the large-amplitude motion state, resulting in a high-amplitude solitary branch response and thereby lowering its vibration absorption efficiency. In this study, the small-amplitude control of the NES nonlinear vibration absorption system has been studied by using the open-loop-plus-nonlinear-closed-loop (OLPNCL) method. First, the dynamic equation of the NES nonlinear vibration-absorbing system was formulated, and its global behavior was analyzed. The regulations of global features and coexisting attractors were found out. Second, the migration between different attractors was carried out under the OLPNCL control, which can ensure that the system always works at the lowest line spectrum intensity and the best overall vibration absorption performance. Finally, the simulation results verify the feasibility and effectiveness of the OLPNCL method and achieve effective vibration absorption in the low-frequency range and line spectrum control under variable operating conditions.